Soil gas radon emissions and volcanic activity at El Hierro (Canary Islands): The 2011‐2012 submarine eruption. (28th February 2013) - Padilla, Germán D.; Hernández, Pedro A.; Padrón, Eleazar; Barrancos, José; Pérez, Nemesio M.; Melián, Gladys; Nolasco, Dácil; Dionis, Samara; Rodríguez, Fátima; Calvo, David; Hernández, Iñigo
Abstract: [1] Soil gas Radon ( 222 Rn) and Thoron ( 220 Rn) activities have been continuously measured during the period of the recent volcanic unrest that occurred at El Hierro, Canary Islands, at two different monitoring stations, namely HIE02 and HIE03. Significant increases in soil 222 Rn activity and 222 Rn/ 220 Rn ratio from the soil were observed at both stations prior to the 2011‐2012 submarine eruption off the coast of El Hierro, showing the highest increases before the eruption onset and before the occurrence of the strongest seismic event (M = 4.6). Statistical analysis showed that the long‐term temporal trend of filtered radon data matched closely that of seismic energy release during the volcanic unrest. The observed increases of 222 Rn are related to the rock fracturing processes (seismic activity) and the magmatic CO2 outflow increase, as observed in HIE03 station. Key Points: Increases in soil Rn activity were observed before the submarine eruption onset